2015
DOI: 10.4137/geg.s31479
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Angiotensin-1 Converting Enzyme Insertion/Deletion and α-Actinin-3 Codon 577 Polymorphisms in Turkish Male Soccer Players

Abstract: Angiotensin-1 converting enzyme (ACE) gene and α-actinin-3 (ACTN3) gene polymorphisms are considered to be the most important candidate genes for genetic predisposition to human athletic performance. In the present study, we aimed to analyze the distribution of ACE and ACTN3 polymorphisms for the first time in male Turkish soccer players. In this prospective study, our cohort consisted of 25 professional players, all with Turkish ancestry. Polymerase chain reaction (PCR)-restriction length polymorphism was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 27 publications
(34 reference statements)
4
19
2
2
Order By: Relevance
“…Our study suggests that individuals with DD and ID genotypes are more predisposed to greater physical strength and power due to the presence of the D allele. Concordantly, our findings are in agreement with the studies made in Australia and Turkey (Ulucan et al, 2015;Jacob et al, 2018). In a Serbian study with female soccer players, there was a high prevalence of the DD genotype, suggesting that individuals with this genotype tend to perform better in soccer (Jeremic et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Our study suggests that individuals with DD and ID genotypes are more predisposed to greater physical strength and power due to the presence of the D allele. Concordantly, our findings are in agreement with the studies made in Australia and Turkey (Ulucan et al, 2015;Jacob et al, 2018). In a Serbian study with female soccer players, there was a high prevalence of the DD genotype, suggesting that individuals with this genotype tend to perform better in soccer (Jeremic et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we showed that the distribution of the ACTN3 genotypes and alleles in the Iranian population is similar to those observed in several reported groups of Russian, Brazilian, and Turkish populations [10,24,26]. There were no statistically significant differences noted in the allelic frequencies between elite soccer players and control group participants, though sample size limitations prevented a conclusive analysis in this regard.…”
Section: Discussionmentioning
confidence: 67%
“…A study on Turkish male soccer players revealed that the frequencies of ACTN3 genotypes were 20, 36, and 44 for XX, RX, and RR, respectively, which agrees with the results of this study for each genotype [24]. In the Turkish study, an allelic frequency was found to be 31 (62%) and 19 (38%) for R and X alleles of ACTN3, respectively, which is similar to our findings (107 (59.4%) R and 73 (40.6%) X alleles).…”
Section: Discussionmentioning
confidence: 99%
“…Since years, many of scientists study the role of Insertion/ Deletion polymorphism and their correlation between genetic and physiological backgrounds in sportspeople. Most research was concentrated on polymorphism in angiotensin converting enzyme (ACE) among athletes [3236], swimmers [1,37,38], football players [39], volleyball players [24,40] or ball games players [41]. There is no research relating to ACE polymorphism among horse riders.…”
Section: Discussionmentioning
confidence: 99%